The drivers for entry and expansion modes of U.S.- based MNES in Brazil - Pimenta, Gustavo Duarte (2012)
The drivers for entry and expansion modes of multinational enterprises (MNEs) have been studied by several authors over the last decades but empirical results have been historically mixed. More recently, Hennart (2009) argued that the reason for the inconsistent results to date resided in the fact that prior theories assumed that local markets could be freely accessed based on a unilateral decision by the MNEs, and then proposes an alternative framework in which the entry and expansion modes of MNEs in foreign countries are a solution based on the relative efficiency of both markets. In this study, the proposed framework is tested against the prior theories based on investments made by U.S.-based MNEs in Brazil from 2005 to 2010. The results suggest that the local market characteristics, more specifically the concentration ratio at the firm and asset levels, are indeed important to influence the entry and expansion mode of U.S.-based MNEs in Brazil, reinforcing the argument against MNEs-centric theories. However, differently from Hennart’s proposition, we were not able to confirm the hypotheses that the MNEs skills are relevant to influence the final solution. We have also tested whether the difference in growth rate between the two countries could be a driver for MNEs to favor acquisition over greenfield given the opportunity cost of postponing the investments. The test result, based on our sample, was not able to confirm this hypothesis.